1982
DOI: 10.1093/ajcn/36.3.546
|View full text |Cite
|
Sign up to set email alerts
|

The validity of a telephone-administered 24-hour dietary recall methodology

Abstract: This study assesses the operational feasibility and validity of a unique telephone-administered 24-h dietary recall methodology. Dietary interviews were conducted by telephone with 204 low-income elderly subjects. Food portion size estimation was done using a two-dimensional food portion visual aid the that was mailed to respondents' homes. The mean intakes and distributions of nine nutrients among males and females in the research sample were compared with those reported in the 1971 to 1974 Health and Nutriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
4

Year Published

1987
1987
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(30 citation statements)
references
References 8 publications
0
26
0
4
Order By: Relevance
“…13 National surveys have used telephone 24-hour recalls. 12 Among adults, numerous studies have indicated that dietary recall information obtained by telephone was, in general, similar to or indicated slightly greater mean intakes than information from in-person dietary recalls in previous national surveys, 14,15 food records, 16 and in-person dietary recalls. 17-21 However, these studies lacked true validation because they compared one self-report method with another self-report method, without investigators knowing the respondents' actual consumption.…”
Section: Introductionmentioning
confidence: 90%
“…13 National surveys have used telephone 24-hour recalls. 12 Among adults, numerous studies have indicated that dietary recall information obtained by telephone was, in general, similar to or indicated slightly greater mean intakes than information from in-person dietary recalls in previous national surveys, 14,15 food records, 16 and in-person dietary recalls. 17-21 However, these studies lacked true validation because they compared one self-report method with another self-report method, without investigators knowing the respondents' actual consumption.…”
Section: Introductionmentioning
confidence: 90%
“…The multi-pass, 24-hour dietary recall methodology has established validity and reliability. 29,30 Participants received a 20-minute training in portion size estimation using a Food Portion Visual, 31 with the addition of food models, dishes and utensils, then completed their first 24-hour dietary recall. The remaining two recalls occurred within 15 days.…”
Section: Dietary Intakementioning
confidence: 99%
“…Traditionally, 24 h dietary recall has been recorded by a face-to-face interview, but interviews conducted by telephone have become increasingly common (Andersson & Rossner, 1996;Bogle et al, 2001;Tran et al, 2000;Fox et al, 1992;Casey et al, 1999) and are considered as a feasible alternative to expensive and time-consuming face-to-face methods (Fox et al, 1992;Posner et al, 1982).…”
Section: Introductionmentioning
confidence: 99%